2021
DOI: 10.1080/21655979.2021.1972081
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of pivotal biomarkers, immune cell infiltration and therapeutic drugs for steroid-induced osteonecrosis of the femoral head

Abstract: Steroid-induced osteonecrosis of the femoral head (SONFH) is a progressive disease that leads to an increased disability rate. This study aimed to ascertain biomarkers, infiltrating immune cells, and therapeutic drugs for SONFH. The gene expression profile of the GSE123568 dataset was downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) were identified using the NetworkAnalyst platform. Functional enrichment, proteinprotein interaction network (PPI), and module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, these studies also present some defects, such as inability to accurately interpret high-throughput sequence data to ensure that a certain deviation exists between PCR verification data and the data significance. [ 9 , 10 ] In the present study, we explored the signaling pathways regulating development of early SONFH and predicted diagnostic biomarkers in peripheral blood from this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies also present some defects, such as inability to accurately interpret high-throughput sequence data to ensure that a certain deviation exists between PCR verification data and the data significance. [ 9 , 10 ] In the present study, we explored the signaling pathways regulating development of early SONFH and predicted diagnostic biomarkers in peripheral blood from this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…64 During the progression of GIONFH, large numbers of chronic inflammatory cells may infiltrate into the peripheral blood and necrotic zone. 65 Multiple studies [66][67][68] evaluated immune infiltration in serum by analyzing GSE123568 which enrolled thirty patients with GIONFH and ten healthy controls, and found decreased infiltration of memory B cells and activated dendritic cells. It could be noticed that macrophages (M0, M1 and M2) were not significantly enriched in the GIONFH group.…”
Section: Immune Infiltration and Macrophage Distribution In Gionfh Im...mentioning
confidence: 99%
“…IL-9 secreted by Th2, Th9 and Th17 cells upregulates inflammatory factors and enzymes related to cartilage degradation, promoting ONFH progression ( 42 , 81 ). High numbers of CTLs infiltrate areas of osteonecrosis and contribute to it ( 24 ). They promote interactions between T cells and osteoclasts and enhance the activity of osteoclasts by secreting cytotoxic T lymphocyte-associated protein 4 (CTLA-4) ( 79 ).…”
Section: Immune Cells and Osteonecrosismentioning
confidence: 99%
“…In the past, osteonecrosis was considered to result from the death of osteoblasts and osteocytes as well as abnormal activation of osteoclasts. However, studies have found a close link between abnormal immune responses and immune cell infiltration in osteonecrotic tissues, which show signs of uncontrolled inflammation (23)(24)(25)(26)(27)(28). How various immune cells regulate inflammation in osteonecrosis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%